2020
DOI: 10.1002/2211-5463.12906
|View full text |Cite
|
Sign up to set email alerts
|

Human salivary histatin‐1 (Hst1) promotes bone morphogenetic protein 2 (BMP2)‐induced osteogenesis and angiogenesis

Abstract: Large‐volume bone defects can result from congenital malformation, trauma, infection, inflammation and cancer. At present, it remains challenging to treat these bone defects with clinically available interventions. Allografts, xenografts and most synthetic materials have no intrinsic osteoinductivity, and so an alternative approach is to functionalize the biomaterial with osteoinductive agents, such as bone morphogenetic protein 2 (BMP2). Because it has been previously demonstrated that human salivary histatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…Collectively, our findings uncover a novel role for Histatin-1 in promoting osteoinduction, which paves new avenues to explore its effects in bone regeneration. It should be mentioned that, although the data shown here indicate a moderate osteoinductive effect of Histatin-1, as compared with standard osteoinductive factors, such as BMP-2 (Sun, Shi, Shen et al, 2020), this does not necessarily imply that the performance of Histatin-1 in bone regeneration is moderate or poor at the clinical level. This is because bone regeneration relies on multiple cellular and molecular phenomena regulated in a temporal and spatial manner (Marsell & Einhorn, 2011).…”
Section: F I G U R Econtrasting
confidence: 57%
See 2 more Smart Citations
“…Collectively, our findings uncover a novel role for Histatin-1 in promoting osteoinduction, which paves new avenues to explore its effects in bone regeneration. It should be mentioned that, although the data shown here indicate a moderate osteoinductive effect of Histatin-1, as compared with standard osteoinductive factors, such as BMP-2 (Sun, Shi, Shen et al, 2020), this does not necessarily imply that the performance of Histatin-1 in bone regeneration is moderate or poor at the clinical level. This is because bone regeneration relies on multiple cellular and molecular phenomena regulated in a temporal and spatial manner (Marsell & Einhorn, 2011).…”
Section: F I G U R Econtrasting
confidence: 57%
“…Interestingly, a more recent study by Sun et al (Sun et al., 2020) showed that Histatin‐1 improves osteoinductive properties of BMP‐2 in a preclinical model. However, that study was conceived on the basis that Histatin‐1 is a proangiogenic factor, but not that the peptide itself was osteoinductive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these data suggest that Hst1 does not enhance osteogenic differentiation, thus bearing no osteoinductivity. On the other hand, in our recent in vivo study, Hst1 significantly promotes angiogenesis and osteogenesis under the stimulation of BMP2 in an ectopic bone induction model (Sun P. et al, 2020). Such an effect of Hst1 on osteogenesis may be attributed to the stimulating effect of Hst1 on angiogenesis (Torres et al, 2017) that favors bone regeneration (Grosso et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Among natural antimicrobial peptides, hBDs are expressed in oral bone (Warnke et al, 2006) (Warnke et al, 2013). In addition, hBDs and histatin-1 promoted bone regeneration and prevented infection (Lee et al, 2018;Peng et al, 2020;Sun et al, 2020).…”
Section: Natural Antimicrobial Peptidesmentioning
confidence: 99%